Does Moral Practice Matter in Restraining Juvenile Delinquency and Drug Addiction in the Socialization Process? - Hossain, Alomgir (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2026)
This study examines the role of moral practice in restraining juvenile delinquency and drug addiction within the socialization process. Adolescence is a critical developmental stage in which individuals are highly influenced by family, peers, educational institutions, and broader social environments. Using a qualitative research design, this study collected primary data through in-depth interviews and focus group discussions with juveniles, including those involved in delinquency and substance use, while secondary data were obtained from academic literature, legal documents, and relevant reports. The data were analyzed using thematic analysis to identify key patterns related to moral development and deviant behavior. The findings reveal that moral practice, particularly when reinforced within family environments through supervision, communication, and religiosity, plays a crucial protective role in reducing involvement in delinquent activities and drug use. Adolescents raised in morally structured and religiously oriented families demonstrated stronger self-control and resistance to negative behaviors. In contrast, weak parental supervision, unstable family conditions, peer pressure, and exposure to harmful digital content were identified as major risk factors contributing to delinquency and addiction. The study also highlights that religiosity functions as a supportive mechanism by strengthening internal moral beliefs and guiding behavior, although its effectiveness depends on broader social contexts. Overall, the study concludes that moral practice is most effective when integrated with strong social support systems. Therefore, comprehensive prevention strategies should incorporate family-based moral education, school engagement, and community interventions to address the root causes of juvenile delinquency and drug addiction.